Compound probiotics promote the growth of piglets through activating the JAK2/STAT5 signaling pathway - Li, Zhiyuan; Dai, Xueyan; Yang, Fan; Zhao, Weina; Xiong, Zhiwei; Wan, Wengen; Wu, Guoyun; Xu, Tianfang; Cao, Huabin (Frontiers in Microbiology, 2025)
IntroductionComposite probiotics are characterized by their non-resistance, no residues, non-toxic effects, and pollution-free nature. To investigate their application capability in piglets, this study aims to explore the effects of composite probiotics on the growth performance and related physiological indicators of piglets.MethodsSixteen 30-day-old healthy weaned “Duroc × Landrace × Large White” piglets were randomly divided into a control group and a composite probiotic (CP) group. The CP group was supplemented with 2 mg·kg-1 of composite probiotics in the basal diet. After 120 days, the growth performance, serum biochemical parameters, hepatic hormones, and expression levels of JAK2/STAT5 signaling pathway-related factors were measured in each group.ResultsThe average daily gain of piglets in the CP group significantly increased, and the feed conversion ratio significantly decreased (p < 0.05). Among the serum biochemical parameters, the levels of triglyceride (TG), aspartate aminotransferase (AST), total cholesterol (TC), and alanine aminotransferase (ALT) were all elevated. Additionally, the levels of growth hormone, insulin, thyroid-stimulating hormone, and triiodothyronine also significantly increased. Furthermore, the addition of composite probiotics upregulated the expression levels of GHR, JAK2, STAT3, STAT5a, and STAT5b.DiscussionIn conclusion, composite probiotics effectively promote the growth performance of piglets by activating the JAK2/STAT5 signaling pathway. These findings provide a theoretical basis for the application of composite probiotics in piglet feeding.